Modulation of β‐Hairpin Peptide Self‐Assembly: A Twenty‐Residue Poly‐l β‐Hairpin Modified Rationally as a Mixed‐l, d Hydrolase. Issue 9 (27th June 2016) - Goyal , Bhupesh; Srivastava , Kinshuk Raj; Patel , Kirti; Durani, Susheel
Abstract: The building blocks of protein structure are defined stereochemically and have remained frozen to only poly‐l alphabet. The D‐enantiomer can be explored to diversify shapes of proteins stereochemically and diversity in shape may enhance proteins in the scope of functional design. Illustrating the scope, we describe here design of a hydrolase mimic over twenty L‐ and D‐α‐amino‐acid residues. The design is accomplished by mutating canonical poly‐L β‐hairpin in a pair of cross‐strand residues to D‐stereochemical structure to provide a bend to β‐hairpin structure that allows its elaboration as a monomer freely soluble in water. The aromatic residues were suitably positioned in the designed mimic to stabilize the molecular fold and to bind aromatic substrate using π–π interaction. The catalytic triad residues were positioned in close proximity for hydrolysis of aromatic‐anchored ligand. The designed peptide variants are proven to bind p ‐nitrophenyl phosphate using fluorescence studies and hydrolyze p ‐nitrophenyl acetate using UV–based enzyme kinetic assays. The study thus highlights the role of stereochemistry in design of novel folds with desired function. Abstract : Cartoon representation of rationally designed stereochemically‐bent twenty‐residue β‐hairpin peptide as a protein and a hydrolase mimic from twenty‐residue poly‐L β‐hairpin. The cross‐strand residues (Leu5, Val16) mutated from LL‐to‐DD structure to promote a monomolecular fold, aromatic residues (Phe1, Trp12, Tyr20) to stabilize molecular fold and for substrate binding, catalytic triad residues (His3, Glu7, Ser18) for aromatic‐anchored substrate hydrolysis are shown in the stick representation.